Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12984-020-00773-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between accelerometry and general compensatory movements of the upper limb after stroke

Abstract: Background Standardized assessments are used in rehabilitation clinics after stroke to measure restoration versus compensatory movements of the upper limb. Accelerometry is an emerging tool that can bridge the gap between in- and out-of-clinic assessments of the upper limb, but is limited in that it currently does not capture the quality of a person’s movement, an important concept to assess compensation versus restoration. The purpose of this analysis was to characterize how accelerometer vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 47 publications
(94 reference statements)
1
30
0
Order By: Relevance
“…However, full-body motion capture suits are less suitable for long-term measurements than bilateral wrist sensors. Therefore, sensor measures from wrist-worn accelerometry that do not only reflect quantity but also the quality of UL activity might be interesting to distinguish compensation versus restoration [ 15 ]. It was recently shown that persons who move the ULs more often and with more variability tend to move with fewer compensations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, full-body motion capture suits are less suitable for long-term measurements than bilateral wrist sensors. Therefore, sensor measures from wrist-worn accelerometry that do not only reflect quantity but also the quality of UL activity might be interesting to distinguish compensation versus restoration [ 15 ]. It was recently shown that persons who move the ULs more often and with more variability tend to move with fewer compensations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, next to the contribution to and intensity of UL activity, there is the variability of UL movement, quantified by the variation ratio. Although this variable has been explored to a lower extent [ 4 ], it may be important in assessing daily life UL activity as it is correlated with movement quality [ 15 ]. It seems that individuals who move the UL more in daily life in terms of time and variability tend to move with fewer compensations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second most complex model included 9 UL performance variables, excluding the three variables calculated from the 30Hz data that are proposed to measure quality of UL activity (6, 24-26) (see Table 1). These variables were removed because they are more complex to calculate, have not been validated in clinical populations (22), and did not add relevant information to the analysis. For the 7 and 5 input variable models, the decision was made to maintain at least one performance variable from each of the other four aspects of UL performance (duration, magnitude, variability and symmetry) to capture the dimensionality of UL performance in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…These variables collectively inform clinician scientists about the real-world activity performance. The numerous variables calculated from accelerometers measure different aspects of UL performance, such as: (1) duration (7,20); (2) magnitude (12,21,22); (3) variability (12,23); (4) symmetry or laterality (3,7,9); and (5) quality of movement (6,(24)(25)(26). Each UL performance variable conveys slightly different information about the collective nature of UL use, with a single variable providing only part of the picture (6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they found that out-of-clinic measurements had stronger relationships with compensatory movements compared with in-clinic measurements. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%